The evolution of Australian intensive care and its related costs: A narrative review. Issue 5 (September 2018) - Thompson, Kelly; Taylor, Colman; Forde, Kevin; Hammond, Naomi
Abstract: Objective: To conduct a narrative review on the evolution of intensive care and the cost of intensive care services in Australia. Review method: A narrative review using a search of online medical databases and grey literature with keyword verification via Delphi-technique. Data sources: Using Medical Subject Headings and keywords (intensive care, critical care, mechanical ventilation, renal replacement therapy, extracorporeal membrane oxygenation, monitoring, staffing, cost, cost analysis) we searched MEDLINE, PubMed, CINAHL, Embase, Google and Google Scholar. Results: The search yielded 30 articles from which we provide a narrative synthesis on the evolving intensive care practice in relation to key service elements and therapies. For the review of costs, we found five relevant publications and noted significant variation in methods used to cost ICU. Notwithstanding the limitations of the methods used to cost all publications reported staffing as the primary cost driver, representing up to 71% of costs. Conclusion: Intensive care is a highly specialised medical field, which has developed rapidly and plays an increasingly important role in the provision of hospital care. Despite the increasing importance of the specialty and the known resource intensity there is a paucity of data on the cost of providing this service. In Australia, staffing costs consistently represent the majority of costs associated with operating an ICU. This finding should be interpreted cautiously given the variation of methods used to cost ICU services and the limited number of available studies. Developing standardised methods to consistently estimate ICU costs which can be incorporated in research into the cost-effectiveness of alternate practice is an important step to ensuring cost-effective care.